Thalictrum foetidum L. in the steppe zone of Ukraine: new findings, ecological and syntaxonomical peculiarities (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
New findings of a rare and endangered species Thalictrum foetidum L. (Ranunculaceae) in the steppe zone of Ukraine are reported. For the territory of the "Buzky Guard" National Natural Park in the Mykolaiv region, we rediscovered the only known locality from this area in the vicinity of Bogdanivka village. Also, we found a new locality near the Lviv village. In the National Natural Park “Kamianska Sich” we found a new for the Kherson Region and southernmost in Ukraine locality of Th. foetidum. We give the description of these localities, their ecological and syntaxonomical peculiarities. In general, all the localities we found in the steppe zone are characterized by the presence of outcrops as granitic ones on the territory of "Buzky Gard" National Nature Park and limestone outcrops on the territory of "Kamyanska Sich" National Nature Park. All the populations were overgrown with shrubs and were shaded. All of them occurred on steep and medium-steep slopes (20–60°) of the northern and north-eastern exposures. On the territory of "Kamyanska Sich" National Nature Park Th. foetidum grows in communities of the class Festuco-Brometea Br.-Bl. et Tx. ex Soo 1947. In the "Buzky Guard" National Nature Park the syntaxonomic position of Th. foetidum is much more diverse. In addition to steppe communities, it was also found in communities of the class Crataego-Prunetea Tx. 1962, transitional vegetation between Crataego-Prunetea and Festuco-Brometea, as well as in communities of chasmophytic vegetation of classes Asplenietea trichomanis (Br.-Bl. in Meier et Br.-Bl. 1934) Oberd. 1977 and Polypodietea Jurko et Peciar ex Boșcaiu, Gergely et Codoreanu in Rațiu et al. 1966. Th. foetidum in the steppe zone is extremely rare and therefore its populations require further study and application of conservation measures.
Keywords: Red Data Book of Ukraine, “Kamyanska Sich” National Nature Park, Buzky Gard